Ted Lasso : the Richmond way [videorecording (DVD)] - Sudeikis, Jason; Lawrence, Bill, 1969-; Hunt, Brendan, 1972-; Kelly, Joe, 1972- (Warner Bros. Entertainment Inc., 2024)
In a bitter divorce settlement from her billionaire husband, Rupert Mannion, Rebecca Welton becomes the new owner of British football club AFC Richmond. She's assisted by her Director of Football Operations, Higgins, who formerly worked for her husband. Her first order of business is to fire the team's current manager and replace him with an idealistic all-American football coach, Theodore 'Ted' Lasso. Ted and his friend, assistant coach Beard, cross the pond to take up the management of the team's 'long, albeit modest' history. Richmond is about to change the way they're doing things, and from now on, that way is the Lasso way.